2015
DOI: 10.3855/jidc.6627
|View full text |Cite
|
Sign up to set email alerts
|

Virology research in a Latin American developing country: a bibliometric analysis of virology in Colombia (2000–2013)

Abstract: Introduction: Bibliometric analysis demonstrates that the virology research in Latin America has increased. For this reason, the objective of this study was to evaluate Colombian publications on viruses and viral diseases in indexed journals during the period from 2000 to 2013. Methodology: The bibliographic data were collected from MedLine, SciELO, LILACS and Scopus databases. The database was constructed in Excel descriptive statistics. The SCImago Journal Rank (SJR) was evaluated using the SCImago Journal &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
1
9
0
1
Order By: Relevance
“…In this study, the current knowledge on AIVs in Latin America was reviewed and several gaps of knowledge were identified. In addition, our review illustrates the strengthening of links between Latin American and non-Latin American research groups over time, which in a globalized world is required to strength science and is consistent with another bibliometric analysis published recently [38]. In our study, inter-institutional cooperation was observed in more than 80% of the publications analysed, a fact that is of great importance because multinational efforts are needed to understand the complexity of the ecology and epidemiology of AIVs [89].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, the current knowledge on AIVs in Latin America was reviewed and several gaps of knowledge were identified. In addition, our review illustrates the strengthening of links between Latin American and non-Latin American research groups over time, which in a globalized world is required to strength science and is consistent with another bibliometric analysis published recently [38]. In our study, inter-institutional cooperation was observed in more than 80% of the publications analysed, a fact that is of great importance because multinational efforts are needed to understand the complexity of the ecology and epidemiology of AIVs [89].…”
Section: Discussionsupporting
confidence: 87%
“…At this point, the articles that did not meet the previously established criteria were excluded. As previously reported [38], two researchers independently selected the publications and filtered the information to enhance the methodological strength, and disagreements were resolved during public discussions with the research team.…”
Section: Methodsmentioning
confidence: 99%
“…The mean number of signing authors per article was 2.04, a slightly lower figure than in other fields (8,9); this maybe due to the early start-date of the period analyzed (1988), since the number of signatures per article has grown annually. This progressive increase might be due to a growing need for larger numbers of participants in research initiatives in order to conduct innovative studies of quality, a tendency that has been observed in other specialized fields (7).…”
Section: Discussionmentioning
confidence: 66%
“…Los expertos en infecciones virales en Colombia contribuyen permanentemente a responder preguntas relacionadas con la emergencia de infecciones, muestra de lo cual es la publicación de más de 100 articulos al año sobre temas relacionados (21), por ejemplo, la descripción cada vez más profunda de los agentes patógenos existentes y de otros nuevos, el estudio de la evolución viral hacia una mayor virulencia, de la forma en que los viajes locales o internacionales y el comercio mundial afectan la dispersión de los virus, así como de los casos en los que los virus cruzan las barreras de las especies. Además, la relevancia creciente de las infecciones virales en veterinaria, dado su impacto en la producción pecuaria y en la convivencia con mascotas, merece especial atención.…”
Section: Papel De La Virología En La Investigación De Las Enfermedadeunclassified